Wagons West : off to Oregon - Chambers, Catherine E.; Smolinski, Dick (Mahwah, N.J. : Troll Associates, 1984)
Two children travel with their older brother across the country by wagon train from Virginia to the Oregon Territory.
Keywords: Overland journeys to the Pacific -- Fiction; Frontier and pioneer life -- Fiction